Phospholipase activity and virulence of pathogenic leptospirae - Volina, E G; Levina, L F; Soboleva, G L (Journal of hygiene, epidemiology, microbiology, and immunology, 1986)
Results of investigation of phospholipase activity and virulence of pathogenic leptospirae on a solid nutrient medium using the method of agar layers with 1% of L-lecithin in the medium of the second layer are presented. It has been demonstrated that only one zone of translucent medium is formed around the colonies of pathological leptospirae, which is obviously due to the release of phospholipase A. The examined virulent strains of pathogenic leptospirae were found to exhibit greater phospholipase activity (width of the translucent zones being 5.0 +/- 0.34 mm) than the avirulent strains (width of the zones being 1.5 +/- 0.11 mm).
Keywords: fosfatidylcholiny; fosfolipasy; kultivační média; Agar; Phosphatidylcholines; Leptospira; Culture Media; Phospholipases A; Phospholipases; agar; fosfolipasy A